2010
DOI: 10.2136/vzj2009.0163
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis of Hydrologic Time Series Data using the Hilbert–Huang Transform

Abstract: For the analysis of me series data from hydrology, we used a recently developed technique that is by now widely known as the Hilbert-Huang transform (HHT). Specifi cally, it is designed for nonlinear and nonsta onary data. In contrast to data analysis techniques using the short-me, windowed Fourier transform or the con nuous wavelet transform, the new technique is empirically adapted to the data in the following sense. First, an addive decomposi on, called empirical mode decomposi on (EMD), of the data into ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…Application to fi eld data corroborated these fi ndings and showed that the proposed approach is useful in estimating shallow soil properties using areal infrared measurements. Rudi et al (2010) applied the Hilbert-Huang transform (HHT) to long-term hydrologic time series of river discharge to extract information on local patterns and structures. Th e advantage of HHT over commonly applied Fourier and wavelet analyses is its applicability to nonuniform time grids.…”
Section: Methods For Characterizing Spa Al and Temporal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Application to fi eld data corroborated these fi ndings and showed that the proposed approach is useful in estimating shallow soil properties using areal infrared measurements. Rudi et al (2010) applied the Hilbert-Huang transform (HHT) to long-term hydrologic time series of river discharge to extract information on local patterns and structures. Th e advantage of HHT over commonly applied Fourier and wavelet analyses is its applicability to nonuniform time grids.…”
Section: Methods For Characterizing Spa Al and Temporal Structuresmentioning
confidence: 99%
“…Rudi et al (2010) applied the Hilbert–Huang transform (HHT) to long‐term hydrologic time series of river discharge to extract information on local patterns and structures. The advantage of HHT over commonly applied Fourier and wavelet analyses is its applicability to nonuniform time grids.…”
Section: Content Of the Special Sectionmentioning
confidence: 99%
“…The time-frequency distribution of the amplitude is designated as the Hilbert amplitude spectrum (or Hilbert spectrum) H(x,t), which can be defined as (Rudi et al 2010) Hðx; tÞ ¼ H½xðtÞ; t ¼ A k ðtÞ on the curve f½t; xðtÞ : t 2 Rg…”
Section: Hilbert Transform (Ht) and Normalization Schemementioning
confidence: 99%
“…To rectify such issues a normalization of Hilbert transform was proposed by Huang et al (2009b). In recent past, the HHT method gaining popularity to analyse the hydro-climatic time series signals worldwide (Huang et al 2009a;Rudi et al 2010;Massei and Fournier 2012;Antico et al 2014;Adarsh and Janga Reddy 2015b). Few studies also applied the EMD procedure for the decomposition of hydrologic time series from India Raghukanth 2005, 2006;Karthikeyan and Nagesh Kumar 2013), but none of the studies used advanced variants of HHT for performing spectral analysis of hydro-climatic data.…”
mentioning
confidence: 99%
“…In hydrological modelling, in fact, such techniques have been primarily adopted for streamflow modelling and reconstruction (Rodriguez-Iturbe et al, 1971;Humphries et al, 1992) and have not performed well enough compared with traditional modelling frameworks to justify the increase in complexity. On the other hand, other advanced applications of spectral analysis, such as Short-Term Fourier Transform, Wavelets Transform or Hilbert-Huang Transform, were successfully applied to the analysis of non-stationary hydrological series (Kumar and Foufoula-Georgiou, 1997;Kang and Lin, 2007;Rudi et al, 2010) . However, while the latter techniques are designed to localize instantaneous or time-dependent frequencies in the time-frequency domain, demodulation enables the investigation of the time dependence of the amplitude and phase of a given frequency, which makes it perfectly suited for the analysis of trends in the energy associated to the harmonics of interest.…”
Section: Demodulation Of Hydrological Seriesmentioning
confidence: 99%